2018
DOI: 10.1037/abn0000325
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of psychopathy in forensic patients.

Abstract: The question of which features represent the most central components of psychopathy remains unresolved and is the subject of considerable debate. Network analysis, which is a relatively new way to conceptualize mental disorders that emphasizes complex causal systems, provides a means to graphically and quantitatively describe the centrality of the various symptoms of a disorder. We applied association and adaptive LASSO networks on two samples of forensic patients. The first sample included forensic inpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 38 publications
(73 reference statements)
5
44
1
1
Order By: Relevance
“…By analyzing the network of interconnections at the time of admission and unconditional release, it can be made transparent how these factors influence each other and which of these activated factors are the most central and influenceable. In network analysis, risk and protective factors are represented as nodes and the associations between pairs of risk and protective factors are depicted as edges ( Borsboom & Cramer, 2013 ; Preszler et al, 2018 ).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the network of interconnections at the time of admission and unconditional release, it can be made transparent how these factors influence each other and which of these activated factors are the most central and influenceable. In network analysis, risk and protective factors are represented as nodes and the associations between pairs of risk and protective factors are depicted as edges ( Borsboom & Cramer, 2013 ; Preszler et al, 2018 ).…”
Section: The Present Studymentioning
confidence: 99%
“…To our knowledge, no studies on network associations and configuration of risk and protective factors in forensic psychiatric patients have been published so far. Some recent forensic studies have conducted research on network configurations in psychopathy, investigating the structure of core symptoms of psychopathic personality disturbance ( McCuish et al, 2019 ; Preszler et al, 2018 ; Verschuere et al, 2018 ).…”
mentioning
confidence: 99%
“…Based on a Danish sample, this suggests that psychopathic personality disorder may best be conceptualized around the core features of Interpersonal, Affective and Lifestyle components. These findings are in accordance with studies specifically exploring the PCL:SV applying network analysis, where findings showed that it was specifically the affective facet that were central to psychopathy, and that, interpersonal, lifestyle, and antisocial facets generally showed low centrality (Preszler et al ., ). Thus, the results using the PCL:SV lend support to the importance of affective deficits as the primary feature of psychopathy.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been suggested to leave out the criminal behavior factor of the PCL‐R when utilizing this scale to assess psychopathy in clinical practice (Cooke & Sellbom, ; Preszler, Marcus, Edens & McDermott, ; Skeem & Cooke, 2010a). Excluding criminal behavior may support the understanding of the relationship, and particularly a possible functional link, between psychopathy and criminal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…(Richters 1997, 206-207) Simple CFA models represent a mismatch between method and the problem to be tackled. Space precludes detailed discussion, however, there are a growing number of techniques that endeavour to model these complexities including exploratory structural equation modelling (ESEM; Cooke and Sellbom in press) and network analyses (Preszler et al 2018;Verschuere et al 2018). Within ESEM approaches the Independent Clusters Model is eschewed and symptoms are modelled so that they may be underpinned by more than latent factor.…”
Section: From Measurement To Conceptmentioning
confidence: 99%